Compétences clés des futurs enseignants de FLE : l’apport des textes littéraires choisis - Bakešová, Václava (Neofilolog, 2022)
Understanding of literary texts and cultural knowledge acquisition are not the only objectives of French or Francophone literature courses that are part of the university program for future FFL teachers. Reading excerpts of literary texts allows students to develop their key skills, especially their cultural awareness and expression, but also their ability to communicate in a foreign language which is the fundamental goal of language teaching. This study presents an example of pedagogical mediation during which various skill sets (global, professional, key, etc.) are being developed through a number of selected literary texts. Pedagogical mediation is understood as a thoughtful process during which students develop the self-awareness in the role of foreign-language and foreign-culture mediator by acquiring the skills necessary for their personal and professional growth, using the full potential of literary texts. At the same time, by deepening the receptive language skills, reading of texts develops also the productive language skills, i.e. speaking and writing, and to the awareness of students’ didactic thinking. Students’ lesson plans show the level at which they are at the moment on their professional skills development path.